Mengembangkan Pendidikan Multikultural dalam Pembelajaran PAI - Murtadho, Ali (Universitas Islam Negeri Raden Intan Lampung, 2016)
Nowadays multiculturalism becomes an important issue, particularly after a series of conflicts that often occur in this country in recent years. Moving on from the problem, then, initiated a deeper understanding of inclusive, pluralistic, and tolerant becomes a necessity; hopes such cases social conflict leading to anarchy in the name of SARA (Tribe, Religion, Race, Class), and other interests who slipped behind it, is not repeated in the future. These issues are of course not only deals with the problem of how we manage conflict, diversity, and political recognition of the otherness of course. However, more than that, that multiculturalism can be understood as